Analysis of the Role of School Culture in Character Building in accordance with the Social Attitudes of Grade V Students at SD Negeri Jurug Bantul - murniati, ira (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2025)
This study aims to analyze the role of school culture in shaping students’ character in accordance with social attitudes, the influencing factors, and the efforts undertaken. The research method used is descriptive qualitative, with data obtained from principals, teachers, students, as well as observations, interviews, and documentation. The results show that school culture plays an important role in character development through habits of independence, environmental awareness, responsibility, and tolerance. Supporting factors include the habituation of school culture, the role of principals, teachers, and students, while inhibiting factors are student violations, differences in character, and the home environment. Efforts made include collaboration between schools and parents, students’ self-awareness, and the provision of adequate facilities to support school culture activities.